2017
DOI: 10.1590/s0104-12902017160873
|View full text |Cite
|
Sign up to set email alerts
|

Vivência do preconceito racial e de classe na doença falciforme

Abstract: ResumoEsse estudo, descritivo com abordagem qualitativa, tem por finalidade compreender as manifestações de discriminação racial e de classe que ocorrem com pessoas que vivenciam a doença falciforme. Participaram do estudo 33 pessoas. O corpus de análise foi composto do registro das narrativas e observações de campo contidas no Diário de Pesquisa. Os resultados mostraram que o preconceito na área da saúde, muitas vezes, se manifesta por meio do racismo institucional. No âmbito socioeconômico, as pessoas que vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 9 publications
(8 reference statements)
0
8
0
10
Order By: Relevance
“…This reality constitutes a deeply disturbing picture for most people with SCD, since this impairs their self-esteem, leading to the construction and perception of a negative self-image. 21 The medians of the summaries of the physical and mental components on the SF-36 questionnaire among all interviewees (48.19 and 68.00, respectively) revealed that the physical impairment is more pronounced than the psychological. A similar study carried out in Cameroon in 2017 showed means of 47.3 and 41.0 for the physical and mental components, respectively, suggesting worse values in the latter, a finding different from that of the present research study; perhaps this could be explained by the unstable political and social situation in that country.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This reality constitutes a deeply disturbing picture for most people with SCD, since this impairs their self-esteem, leading to the construction and perception of a negative self-image. 21 The medians of the summaries of the physical and mental components on the SF-36 questionnaire among all interviewees (48.19 and 68.00, respectively) revealed that the physical impairment is more pronounced than the psychological. A similar study carried out in Cameroon in 2017 showed means of 47.3 and 41.0 for the physical and mental components, respectively, suggesting worse values in the latter, a finding different from that of the present research study; perhaps this could be explained by the unstable political and social situation in that country.…”
Section: Discussionmentioning
confidence: 94%
“…In the case of young people with SCD, hospitalisations limit their satisfactory school development, making them also stigmatised for being sick and absent. 21 In addition, SCD may create limitations on the practice of sports. For all these reasons, it is perceived that it is necessary to maintain the support of a multidisciplinary team with psychological and social support throughout the school life of this population.…”
Section: Discussionmentioning
confidence: 99%
“…This study highlights that SCD in Campina Grande, Paraíba and its surrounding cities occurs predominantly amongst the mixed and black populations, and evidence shows a clear social vulnerability, which already was demonstrated by other studies. 8,[16][17][18] The affected population occupies the base of the social pyramid and exhibits the worst socioeconomic, epidemiological and educational indicators; it gains the lowest salary, it has the highest unemployment rate, the worst access to healthcare and the lowest participation of GDP, and for this reason it is a victim of the institutional racism, with differenti-ated distribution of services, benefits and opportunities, generating inequalities and inequities. 16 The predominance of SCD among the underprivileged is well documented in many studies on the subject, [18][19][20][21] as well as the low schooling level of caregivers; in some publications, more than 50% of the responsible guardians did not concluded the elementary level of education.…”
Section: Discussionmentioning
confidence: 99%
“…18,24 The psychosocial consequences faced by these individuals must be taken into consideration; they are victims of stigmatization resulting from a triple association between skin color -social classchronic and severe disease. 16 Low self-esteem, social isolation and feelings of hopelessness may occur, contributing to the onset of depression, which also contributes to the increase in pain crises, missed appointments and poor adherence to the treatment. 19 We would like to highlight the high prevalence of SCD cases among patients who are resident outside the follow-up city.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation